Cobalt embedded in nitrogen-doped porous carbon as a robust heterogeneous catalyst for the atom-economic alcohol dehydrogenation to carboxylic acids. (15th April 2021) - Chen, Cheng; Wang, Zhi-Qin; Gong, Yan-Yan; Wang, Ji-Chao; Yuan, Ye; Cheng, Hua; Sang, Wei; Chaemchuen, Somboon; Verpoort, Francis
Abstract: Herein, cobalt embedded in nitrogen-doped porous carbon (Co@NC) was developed as a robust heterogeneous catalyst for the dehydrogenative coupling of primary alcohols and hydroxides. With Co@NC as the first earth-abundant metal/carbon composite material for this transformation, numerous aromatic and aliphatic carboxylic acids were efficiently afforded. Notably, the newly prepared Co@NC was fabricated in a facile and straightforward manner and reused up to 15 recycle rounds without activity decay. It is also worth emphasizing that the catalyst recycling was realized via magnetic separation with no special treatment or activation. Additionally, further experiments elucidated the pivotal role of the cobalt and nitrogen elements dispersed in the carbon matrix as well as the hierarchical porosity (micro-/meso-pores) in the catalytic activity and recyclability. Considering the active sites of Co@NC, we envisioned that the Co–N species was the most active site, while other active sites such as Co–O, Co 0 species and free N-doped carbon were also present, but demonstrating lower activity or stability in comparison with the Co–N species. Additional mechanistic investigations were carried out to gain more insights into the possible reaction pathways. We found that the aldehyde was identified as a crucial intermediate, and two possible pathways were proposed for this catalytic process. Graphical abstract: Image 1 Highlights: Co embedded in nitrogen-doped porous carbon as a robust heterogeneous catalyst. The 1st earth-abundant metal/carbon material for the alcohol dehydrogenation to acids. Recyclable for 15 times by magnetic separation without special treatment/activation. Unique porous structure and well-dispersion of Co and N within the carbon matrix. Investigation of active catalytic sites and reaction pathways.